Alterations in the intestinal microbiome and metabolic profile of patients with cirrhosis supplemented with lactulose, Clostridium butyricum, and Bifidobacterium longum infantis: a randomized placebo-controlled trial - Lu, Haifeng; Zhu, Xiaofei; Wu, Lingyun; Lou, Xiaobin; Pan, Xiaxia; Liu, Bowen; Zhang, Hua; Zhu, Lingxiao; Li, Lanjuan; Wu, Zhongwen (Frontiers in Microbiology, 2023)
Liver cirrhosis is commonly accompanied by intestinal dysbiosis and metabolic defects. Many clinical trials have shown microbiota-targeting strategies represent promising interventions for managing cirrhosis and its complications. However, the influences of the intestinal metagenomes and metabolic profiles of patients have not been fully elucidated. We administered lactulose, Clostridium butyricum, and Bifidobacterium longum infantis as a synbiotic and used shotgun metagenomics and non-targeted metabolomics to characterize the results. Patients treated with the synbiotic for 12 weeks had lower dysbiosis index (DI) scores than placebo-treated patients and patients at baseline (NIP group). We identified 48 bacterial taxa enriched in the various groups, 66 differentially expressed genes, 18 differentially expressed virulence factor genes, 10 differentially expressed carbohydrate-active enzyme genes, and 172 metabolites present at differing concentrations in the Synbiotic versus Placebo group, and the Synbiotic versus NIP group. Bifidobacteria species, especially B. longum, showed positive associations with many differentially expressed genes, but not antibiotic resistance genes, in synbiotic-treated patients. Metabolites profiling demonstrated that synbiotic-treated patients had lower fasting serum oligopeptide concentrations than placebo-treated patients. Pathway enrichment analysis showed the synbiotic significantly affected purine metabolism and aminoacyl-tRNA biosynthesis. And the purine metabolism and aminoacyl-tRNA biosynthesis were no longer significant differences in the Synbiotic group versus the HC group. Only minor differences occurred in phage populations over the course of synbiotic supplementation, except for differences in the relationships between Streptococcus_satellite prophage and bacterial species. This study is the first to report the alterations in the intestinal microbiome and metabolic profile in cirrhotic patients treated Lactulose combined with Clostridium butyricum and Bifidobacterium longum infantis. Although littles influence on clinical parameters, the synbiotic showed a potential benefit to patients by ameliorating intestinal dysbiosis and metabolic defects. Trial registration: URL: https://www.clinicaltrials.gov; Unique identifiers: NCT05687409.